The Nexus of Independent Commissioners, CSR, and Dividend Policy on Firm Value: Profitability as a Moderating Variable - Iqbal Andri Firmansyah; Mia Ika Rahmawati (Politeknik Ganesha Medan, 2026)
This study aims to examine the effects of Independent Commissioners, Corporate Social Responsibility (CSR), and Dividend Policy on Firm value, and to assess the role of Profitability as a moderating variable in this relationship. The object of this study is banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. This study is quantitative research. Using a saturated sample method, the population size equals the sample size: 47 companies with three years observation from 2022-2024 thus it resulting with totalling 141 observations. The data analysis techniques used are multiple linear regression analysis and Moderated Regression Analysis (MRA). The results show that independent commissioners, CSR, and dividend policy have a positive and significant effect on firm value. Furthermore, the MRA test results prove that Profitability can moderate (strengthen) the effect of independent commissioners and dividend policy on firm value. However, Profitability cannot moderate the relationship between CSR and firm value. These findings indicate that investors view CSR disclosure as a long-term sustainability commitment that is independent of the company's annual profit fluctuations.